Explicating the privacy paradox: A qualitative inquiry of online shopping consumers. (January 2020) - Bandara, Ruwan; Fernando, Mario; Akter, Shahriar
Abstract: Online consumers often voice discontent and concern over their privacy and yet fail to take adequate precautions. Nor do they abstain from disclosing information. This study aims to explore this phenomenon which is known as the privacy paradox. Based on semi-structured interviews with online shopping consumers and thematic analysis of data, this paper illuminates the privacy paradox using three themes: psychological distance of privacy, perceived social contracts of privacy, and learned helplessness and privacy empowerment. Our findings contribute to the privacy paradox discourse and provide several implications for consumers, online retailers, and policymakers.